Borehole temperature measurements at MeBo200 drill site GeoB22605-1, Black Sea - Freudenthal, Tim (In: Freudenthal, T (2022): Borehole temperature measurements and drilling data at MeBo200 drill sites in the Black Sea and the South China Sea [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.945432, 2022)
Borehole temperature measurements at site GeoB22605-1 were performed with the sea floor drill rig MARUM-MeBo200 during research expedition M142 in November 2017 at the Danube Deep Sea fan in the Black Sea. A platinum resistance sensor integrated in the 1343 Slimhole Memory Acoustic Tool developed by ANTARES Datasystems GmbH was used to measure the temperature of the fluid within the borehole with 103 mm diameter. The temperature range is –20 to +80 °C, the absolute accuracy within the limits of the measuring range is about 1 °C. The resolution of the temperature measurements is about 0.003 °C. Temperatures were logged with a frequency of 0.5 Hz by a memory adapter with an integrated clock that was synchronized with GPS-time. Borehole logging was conducted during trip out of the drill string. When the drilling operation was completed and the drill string was lifted by about 3.5 m the logging string was dropped into the drill string. After landing on the drill bit the logging string together with the drill string were tripped out of borehole. The depth control system of the drill rig was used to calculate the sensor depth with an accuracy of 0.1%.
Keywords: Black Sea; borehole logging; Borehole temperature; MeBo